2008
DOI: 10.1152/ajpcell.00523.2007
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide facilitates NFAT-dependent transcription in mouse myotubes

Abstract: Intracellular calcium transients in skeletal muscle cells initiate phenotypic adaptations via activation of calcineurin and its effector nuclear factor of activated t-cells (NFAT). Furthermore, endogenous production of nitric oxide (NO) via calcium-calmodulin-dependent NO synthase (NOS) is involved in skeletal muscle phenotypic plasticity. Here, we provide evidence that NO enhances calcium-dependent nuclear accumulation and transcriptional activity of NFAT and induces phosphorylation of glycogen synthase kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 28 publications
(53 reference statements)
9
37
0
2
Order By: Relevance
“…41 A link between NO activity and UMOD expression was confirmed in wild-type mice exposed to a nonselective NOS inhibitor (L-NAME), which resulted in reduced UMOD protein expression in kidney tissue and urine. Of note, NO exerts regulatory control over two transcription factors-nuclear factor of activated T cells 42 and Oct-1 43 -both of which have consensus-binding sites in the promoter region of UMOD. 44 These observations raise the possibility of direct regulation of UMOD expression by NO, a suggestion that certainly warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…41 A link between NO activity and UMOD expression was confirmed in wild-type mice exposed to a nonselective NOS inhibitor (L-NAME), which resulted in reduced UMOD protein expression in kidney tissue and urine. Of note, NO exerts regulatory control over two transcription factors-nuclear factor of activated T cells 42 and Oct-1 43 -both of which have consensus-binding sites in the promoter region of UMOD. 44 These observations raise the possibility of direct regulation of UMOD expression by NO, a suggestion that certainly warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of this enzyme can be inhibited with a high content of nitrogen oxide in the fiber, which acts through the guanylate cyclase mechanism [78]. We have previously shown that the nitrogen oxide level in rat soleus is significantly reduced during gravitational unloading [79].…”
Section: Expression Of Myosin Genes Under Conditions Of Gravitationalmentioning
confidence: 99%
“…Several studies suggest a role of endogenous NO in AMPKand Ca 2ϩ -dependent regulation of PGC-1␣, GLUT4, and mitochondrial genes (119,128). NO is also required for functional overload-induced upregulation of slow myosin heavy chain (MHC; type 1/␤) (182) through modulation of Akt and glycogen synthase kinase-3␤ (GSK-3␤) activities and amplification of CnA/NFAT-dependent signaling (51). In support of this, eNOS Ϫ/Ϫ muscle cells have reduced type 1 MHC expression (52), and low levels of NO donors promote mitochondrial biogenesis, PGC-1␣, and GLUT4 expression in cultured muscle cells (119,145) through a mechanism involving AMPK␣1 activation (Lira VA and Criswell DS, unpublished data).…”
Section: Pgc-1␣ Regulation In Response To Exercisementioning
confidence: 99%